Bopirídeos do Brasil (Crustacea - Isopoda) - Lima, Idalina Maria Brasil (1978)
Provides biological data on the isopods of the Suborder Epicaridea, parasites of the other crustaceans, and makes a detailed study of the Brazilian forms of the Family Bopyridae, the most representative of the group. Some remarks are made on the life cycle of this crustaceans from egg to adult phase, with descriptions of the characteristic larval stages. The different modes of fixation on the host and, the relations parasite-host, are also deal with. Eighteen species of the family Bopyridae are studied, ten of them has been referred previously to Brasil, six are found at the first time on Brazilian waters and two are new for the Science, being erected a new genus for each one.